Students' Knowledge of Climate Change, Mitigation and Adaptation in the Context of Constructive Hope - Ilkka Ratinen (MDPI AG, 2021)
Humanity is living in a climate emergency where climate change should be significantly mitigated; additionally, greater efforts should be made to adapt to it. To date, relatively little research has been carried out on young people's skills in terms of them mitigating and, in particular, adapting to the changes caused by climate change. The complex climate change issues of mitigation and adaptation are conceptually difficult for children because climate change is not directly evidenced in their daily lives. This study focuses on looking at mitigation and adaptation from the perspective of children. Meaning-making coping strategies enable the maintenance of constructive hope regarding climate change. In the present study, elementary and secondary students (n = 950) responded to an online questionnaire. Statistical methods were used to gather data on how students' general knowledge of climate change and their mitigation and adaptation knowledge predicted their constructive hope regarding climate change. This study reveals that the students had a relatively high level of constructive hope and that general climate change knowledge predicted students' constructive hope well.